1999
DOI: 10.1159/000008106
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Signal Abnormalities and Neuropsychological Deficits in Elderly Compressed-Air Divers

Abstract: We investigated the association between MR signal abnormalities of the central nervous system, neuropsychologic performance and exposure indices in 20 experienced elderly compressed-air divers who had no history of neurological decompression illness (DCI). Results of MRI of the brain and psychometric testing were compared with 20 matched healthy commercial employees who never dived: 60% of the divers and 45% of the controls had hyperintense MR abnormalities. Among divers, both the number and the size of abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 13 publications
1
20
0
2
Order By: Relevance
“…Similarly, cognitive dysfunction was identified in Australian abalone divers [3] but this was not confirmed in a follow-up study [4]. There have been other conflicting reports of cognitive dysfunction in divers [5,6]. More consistent observations have been made in Norwegian commercial divers [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, cognitive dysfunction was identified in Australian abalone divers [3] but this was not confirmed in a follow-up study [4]. There have been other conflicting reports of cognitive dysfunction in divers [5,6]. More consistent observations have been made in Norwegian commercial divers [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the present study did not address the potential long-term neurologic hazards 19 being inflicted by asymptomatic ischaemic brain lesions which have also been found to be related to PFO in divers, 11 i.e., the effect of the cumulative cerebral ischaemic burden associated with PFO in divers is unknown. Accordingly, we advise a diver with a 2nd or 3rd degree PFO to refrain from diving.…”
Section: Discussionmentioning
confidence: 91%
“…There is still debate whether different and repeated diving exposures over time may cause long term effects on the nervous system in divers who have not experienced DCS [51][52][53][54][55][56]. Dolmierski [51] found that 30% of a group of air divers had abnormal neurological findings although only half of them had had DSC.…”
Section: Epidemiological Studiesmentioning
confidence: 99%